City Ordinances of Springfield, Mass. 121 (1871) - (:unkn) unknown (My University, 1871)
No. 44. An Ordinance for the Prevention of Injurious Practices in the Streets, §21 Firearms, not to be discharged in streets, &c., except, &c.: "Sect. 21. No person shall discharge any gun, pistol or other firearm in any of the streets, highways, public squares or commons in the city ; provided, this section shall not apply to the use of such weapons in the lawful defense of the person, family or property of any one, or in the performance of any duty required by law, nor to the firing of a salute of cannon or artillery by permission of the mayor and aldermen."
Keywords: DISCHARGE